Comparative Analysis of Testicular Histology and lncRNA–mRNA Expression Patterns Between Landes Geese (Anser anser) and Sichuan White Geese (Anser cygnoides) - Ran, Mingxia; Huang, Huaxuan; Hu, Bo; Hu, Shenqiang; Hu, Jiwei; Li, Liang; He, Hua; Liu, Hehe; Wang, Jiwen (Frontiers in Genetics, 2021)
It is well known that the female goose of Landes goose and Sichuan white goose differ remarkably in their reproductive performance. However, the physiological mechanisms and key genes related to the differences in male goose reproductive capacity between these two breeds have not been reported. In the present study, histological results showed that the testicular organ index and long diameter of seminiferous tubules of Landes goose were significantly larger than that in Sichuan White goose. The analyses of mRNA-lncRNA expression profile showed that compared with Sichuan White goose, a total of 462 differentially expressed mRNAs (DEGs) (173 up-regulated and 289 down-regulated) and 329 differentially expressed lncRNAs (DE lncRNAs) (280 up-regulated, 49 down-regulated) were obtained in Landes goose. Among these DEGs, there were ten spermatogenesis-related and highly expressed (FPKM > 10) DEGs, and except for SEPP1, all of these DEGs were significantly up-regulated in the testes of Landes goose. Functional enrichment analysis indicated that the pathway related to metabolism progress and phosphoinositol signal is the key pathway to regulate the reproductive performance difference between Lande goose and Sichuan white goose. Our result reveals that compared with Sichuan white goose, the spermatogenesis in the testis of Landes goose was more active and this difference may be mainly related to the difference in inositol phosphate signal. These data will contribute to a further understanding of the difference in reproduction performance between the Lande goose and Sichuan white goose and eventually provides a theoretical reference for improving the reproductive performance of the male goose.